2017
DOI: 10.2174/1871527316666170518170422
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived Neurotrophic Factor Promotes Growth of Neurons and Neural Stem Cells Possibly by Triggering the Phosphoinositide 3-Kinase/ AKT/Glycogen Synthase Kinase-3β/β-catenin Pathway

Abstract: Our findings suggested that BDNF contributed to neuronal growth and proliferation and differentiation of NSCs in vitro by stimulating PI3K/AKT/GSK3β/β-catenin pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…At the same time, the receptor of BDNF, tropomyosin receptor kinase B (TrkB), was expressed in NSPCs. It has been reported that BDNF/Akt signaling was related to NSPC growth and differentiation in vitro, and BDNF secretion as well as the phosphorylation of Akt could be induced by different frequency magnetic stimulation, followed by an influence on neuronal cell proliferation (Sabelström et al, 2014;Hossain et al, 2017;Li et al, 2017). Our results confirmed that the phosphorylation of Akt at Thr308 and Ser473 sites was increased upon magnetic stimulation.…”
Section: Discussionsupporting
confidence: 86%
“…At the same time, the receptor of BDNF, tropomyosin receptor kinase B (TrkB), was expressed in NSPCs. It has been reported that BDNF/Akt signaling was related to NSPC growth and differentiation in vitro, and BDNF secretion as well as the phosphorylation of Akt could be induced by different frequency magnetic stimulation, followed by an influence on neuronal cell proliferation (Sabelström et al, 2014;Hossain et al, 2017;Li et al, 2017). Our results confirmed that the phosphorylation of Akt at Thr308 and Ser473 sites was increased upon magnetic stimulation.…”
Section: Discussionsupporting
confidence: 86%
“…Bdnf ) expression (Zhang, Zhang, Deng, et al, ; Zhang, Shi, et al, ; Zhang, Zhang, Yang, et al, ). Also, in human NSCs, Yang et al () showed the ability of BDNF to promote their growth via GSK‐3β‐mediated crosstalk with the WβC‐ signalling pathway, and Li et al () involved the contribution of the PI3K/Akt/GSK‐3β/β‐catenin pathway in BDNF‐induced neuron and NSC growth. Ambrosone et al () documented the ability of optogenetic stimulation to promote cell proliferation and the migration of SVZ neuroblasts into the peri‐infarct cortex, asssociated with increased neuronal differentiation and improvement of long‐term functional recovery after stroke.…”
Section: Therapeutic Modulation Of Wnt/β‐catenin Signallingmentioning
confidence: 99%
“…Physical activity and environmental enrichment regulate the generation of neural precursors in the adult mouse substantia nigra; WβC-AC involvement to be elucidated Klaissle et al (2012) Endurance exercise promotes neuroprotection against MPTP injury via enhanced neurogenesis, antioxidant capacity and autophagy; WβC-AC involvement to be elucidated Jang, kwon, Song, Cosio-Lima and Lee (2018a), Jang et al (2018b) Neural activation Neural activity-induced WβC-AC up-regulates expression of BDNF. Zhang, Zhang, Deng, et al, 2018a Neurotrophic factors BDNF promotes growth of neurons and NSCs, possibly through activation of the PI3K/GSK-3β/β-catenin pathway Li et al (2017) BDNF promotes human neural stem cell growth via GSK-3β-mediated crosstalk with the WβC pathway Yang et al (2016) Optical depolarization…”
Section: Optogeneticsmentioning
confidence: 99%
“…Sevoflurane was also reported to decrease the level of BDNF and induced cognitive impairment in 18 month-old rats [45]. BDNF is critical involved in the differentiation of NSCs from iPSCs [47] and could promote neurons and NSCs growth [48]. We further found that miR-466l -3p directly targets BDNF, leading to the inhibition of the neural differentiation.…”
Section: Discussionmentioning
confidence: 72%
“…Next, we addressed which downstream target gene could be regulated by miR-466l-3p. Brain derived neurotrophic factor (BDNF) is critical involved in the differentiation of iPSCs to NSCs [47] and also promotes growth of neurons and NSCs [48]. Sevoflurane also resulted in significant inhibition BDNF expression and cognitive impairment [45].…”
Section: Bdnf Is Directly Targeted By Mir-466l-3p To Mediate Neural Dmentioning
confidence: 99%